Chromium Complexes with Oxido and Corrolato Ligands: Metal‐Based Redox Processes versus Ligand Non‐Innocence. Issue 48 (19th July 2018) - Garai, Antara; Sobottka, Sebastian; Schepper, Rahel; Sinha, Woormileela; Bauer, Matthias; Sarkar, Biprajit; Kar, Sanjib
Abstract: Metal‐ versus ligand‐centered redox processes and the effects of substituents on the ligands on the spectroscopic properties of the metal complexes are at the heart of research on metal complexes with non‐innocent ligands. This work presents three examples of chromium complexes that contain both oxido and corrolato ligands, with the substituents on the corrolato ligands being different in the three cases. Combined X‐ray crystallographic, electrochemical, UV/Vis/NIR/EPR spectroelectrochemical, and EXAFS/XANES measurements, together with DFT calculations, have been used to probe the complexes in three different redox forms. This combined approach makes it possible to address questions related to chromium‐ versus corrolato‐centered redox processes, and the accessibility (or not) of Cr IV, Cr V, and Cr VI in these complexes, as well as their spin states. To the best of our knowledge, these are the first EXAFS/XANES investigations on Cr‐corrolato complexes in different redox forms, and hence these data should set benchmarks for future investigations on such complexes by this method. Abstract : Metal‐ or ligand‐centered redox? UV/Vis/NIR/EPR spectroelectrochemical and XANES measurements, together with DFT calculations, have been applied to address the issue of chromium‐ versus corrolato‐centered redox processes, and the accessibility (or not) of Cr IV, Cr V, and Cr VI in these complexes, as well as their spin states.